2016
DOI: 10.1111/all.13055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of children's nutritional attitudes before oral food challenges to identify patients at risk of food reintroduction failure: a prospective study

Abstract: Evaluating child's approach towards food before the OFC is a promising approach to identify patients at risk of food reintroduction failure. Furthermore, it underlined the importance of reassessing food consumption in all patients after a negative OFC and supporting patients in the reintroduction of food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…31,32 Even after a negative oral food challenge (OFC), maternal anxiety before the OFC has been found to be correlated to a following limited level of change in the child's nutritional habits. 33 The emotional/ behavioural influence of FA may affect nutritional status over time if fear of having a reaction impacts willingness to eat. A case of an 11-year-old boy with peanut allergy reporting a selective diet related to an anxiety disorder has been described.…”
Section: Anxiety and Fa Managementmentioning
confidence: 99%
“…31,32 Even after a negative oral food challenge (OFC), maternal anxiety before the OFC has been found to be correlated to a following limited level of change in the child's nutritional habits. 33 The emotional/ behavioural influence of FA may affect nutritional status over time if fear of having a reaction impacts willingness to eat. A case of an 11-year-old boy with peanut allergy reporting a selective diet related to an anxiety disorder has been described.…”
Section: Anxiety and Fa Managementmentioning
confidence: 99%
“…In fact, a prospective study that assessed the nutritional attitudes of children with food allergy before and after OFC in relation to their mothers' anxiety showed a negative correlation between anxiety of mothers before OFC and degree of change in nutritional habits of their children after OFC. 18 The authors stated that a positive attitude of mothers toward food before OFC promoted subsequent food reintroduction, which increased children's interest in tasting new foods, and led to favorable changes in nutritional habits. A negative initial maternal attitude, on the other hand, led to an unfavorable attitude in the child.…”
Section: Discussionmentioning
confidence: 99%
“…5,16,17 In addition, it was reported that mothers with a high level of anxiety, even after a negative OFC for their child, were reluctant to reintroduce the offending food. 18 Psychological factors may affect the natural history of food allergy.…”
Section: Introductionmentioning
confidence: 99%
“…47 One trait that has been prospectively identified as associated with failure of reintroduction in children is a lack of interest in eating a new food. 48 Rarely, a patient may react at home after passing an observed OFC. This could be explained by either a higher dose triggering a reaction than was fed in a clinic or cofactors that lowered the triggering threshold.…”
Section: Incorporation Of the Foodmentioning
confidence: 99%